Mucosal BCG delivery provides a spectrum of protection from different Mycobacterium tuberculosis strains across susceptible and resistant mouse backgrounds - Larsen, Sasha E.; Williams, Brittany D.; Pecor, Tiffany; Reese, Valerie A.; Zhu, Zhiyi; Miller, Dana E.; Podell, Brendan K.; Baldwin, Susan L.; Coler, Rhea N. (Frontiers in Tuberculosis, 2024)
Mycobacterium bovis Bacille Calmette-Guérin (BCG) is the sole globally licensed vaccine against tuberculosis despite its relatively moderate protection of acute disease through adolescence. We hypothesize that vaccine efficacy from a mucosal BCG vaccination will be directly influenced by Mycobacterium tuberculosis (M.tb) strain and mouse background. Here we investigated the effectiveness of mucosal BCG vaccination via the intranasal route, in resistant and susceptible mouse strains, to protect against laboratory strain H37Rv and clinical strain HN878 M.tb aerosol challenge. We evaluated both pulmonary and disseminated CFU at 4-weeks post-infection in addition to survival endpoints in C57BL/6, SWR and C3HeB/FeJ mice. Antigen specific T cell responses in the lung post-infection were also evaluated. We observed that in each case intranasal BCG afforded a significant reduction in pulmonary CFU at 4-weeks post-infection compared to matched untreated controls. However, only susceptible mouse strains, SWR and C3HeB/FeJ, demonstrated similarly robust control from bacterial dissemination when CFU in the spleen was evaluated at the same timepoint. In the case of both M.tb H37Rv and M.tb HN878 challenge, intranasal BCG significantly improved survival of each mouse cohort compared to unvaccinated controls. Together these data suggest that there is still much to be learned from the century old vaccine, BCG, and how it drives protection.